2020
DOI: 10.3389/fcimb.2020.602502
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles in Trypanosomatids: Host Cell Communication

Abstract: Trypanosoma cruzi, Trypanosoma brucei and Leishmania (Trypanosomatidae: Kinetoplastida) are parasitic protozoan causing Chagas disease, African Trypanosomiasis and Leishmaniases worldwide. They are vector borne diseases transmitted by triatomine bugs, Tsetse fly, and sand flies, respectively. Those diseases cause enormous economic losses and morbidity affecting not only rural and poverty areas but are also spreading to urban areas. During the parasite-host interaction, those organisms release extracellular ves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(89 citation statements)
references
References 200 publications
(318 reference statements)
1
86
1
1
Order By: Relevance
“…It is noteworthy, that the percentage of TS proteins (22% vs. 7% in EVs of TCT and E, respectively) and the diversity of TS members (groups I-VI vs. group II in EVs of TCT and E, respectively) is remarkably increased in EVs of TCT. Due to the size (80-200 KDa) [38,39] and that they are heavily glycosylated, it could be suggested that they should have an impact on the different mechanical properties found in EVs of both stages.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy, that the percentage of TS proteins (22% vs. 7% in EVs of TCT and E, respectively) and the diversity of TS members (groups I-VI vs. group II in EVs of TCT and E, respectively) is remarkably increased in EVs of TCT. Due to the size (80-200 KDa) [38,39] and that they are heavily glycosylated, it could be suggested that they should have an impact on the different mechanical properties found in EVs of both stages.…”
Section: Discussionmentioning
confidence: 99%
“…Trypomastigotes (MTs and TCTs) and EAs shed a wide number of GPI-anchored surface proteins/glycoproteins such as members of the gp85/TS family, mucins and MASPs (Trocoli Torrecilhas et al, 2009;Cańepa et al, 2012b;Bayer-Santos et al, 2013b;Lantos et al, 2016;Watanabe Costa et al, 2016). These proteins are not secreted by the classical endoplasmic reticulum (ER)/Golgi-dependent secretion pathway, but instead, gradually released into milieu by the action of an endogenous PI-PLC (Andrews et al, 1988), or associated to extracellular vesicles (EVs) involved in host cell invasion, immunomodulation and pathogenesis (Borges et al, 2016;Torrecilhas et al, 2020). EVs can be divided into: microvesicles or ectosomes (100 nm to1 mM), directly originated by budding from plasma membrane, and exosomes (30-100 nM), that are secreted following the fusion of multivesicular endosomes with the membrane at the flagellar pocket (Evans-Osses et al, 2015).…”
Section: Protein Secretion and Extracellular Vesicles Cargomentioning
confidence: 99%
“…In recent years, research efforts have focused increasingly on the development of experimental approaches to the study of the parasitic extracellular vesicles, in response to the recent expansion of interest in the role of LEVs in the pathogenesis of both cutaneous and visceral leishmaniasis [2,6,[82][83][84]. Emerging technologies such as proteomic and bioinformatic analyses have been adapted for the study of the extracellular vesicles released from parasites in vitro [3,[85][86][87][88]. To further our understanding of the Leishmaniahost-cell interactions, a broad-scale analysis of the cargo of their production of extracellular molecules has created very promising perspectives for the development of innovative applications [3,[85][86][87][88].…”
Section: Current and Expected Advances In Leishmania Extracellular Vesicle Researchmentioning
confidence: 99%